Glucose-induced increase in cytoplasmic pH in pancreatic beta-cells is mediated by Na+/H+ exchange, an effect not dependent on protein kinase C. - Juntti-Berggren, L; Arkhammar, P; Nilsson, T; Rorsman, P; Berggren, P (1991)
Glucose-induced changes in cytoplasmic pH (pHi) were investigated using pancreatic beta-cells isolated from obese hyperglycemic mice. Glucose, at concentrations above 3-5 mM, depolarized the beta-cell and increased pHi, cytoplasmic free Ca2+ ([Ca2+]i), and insulin release. This increase in pHi was dependent on the presence of extracellular Na+ and was inhibited by 5-(N-ethyl-N-isopropyl) amiloride, a blocker of Na+/H+ exchange. Stimulation of protein kinase C with phorbol ester also induced an alkalinization. However, when protein kinase C activity was down-regulated, glucose stimulation still induced alkalinization. At 20 mM glucose, 10 mM NH4Cl induced a marked rise in pHi, paralleled by repolarization, inhibition of electrical activity, and decreases in both [Ca2+]i and insulin release. Reduction in [Ca2+]i was prevented by 200 microM tolbutamide, but not by 10 mM tetraethylammonium. At 4 mM glucose, NH4Cl induced a transient increase in insulin release, without changing [Ca2+]i. Exposure of beta-cells to 10 mM sodium acetate caused a persistent decrease in pHi, an effect paralleled by a small transient increase in [Ca2+]i. Acidification per se did not change the beta-cell sensitivity to glucose, not excluding that the activity of the ATP-regulated K+ channels may be modulated by changes in pHi.